The 2013 International Joint Conference on Neural Networks (IJCNN) 2013
DOI: 10.1109/ijcnn.2013.6706784
|View full text |Cite
|
Sign up to set email alerts
|

Robot coverage control by evolved neuromodulation

Abstract: Abstract-An important connection between evolution and learning was made over a century ago and is now termed as the Baldwin effect. Learning acts as a guide for an evolutionary search process. In this study reinforcement learning agents are trained to solve the robot coverage control problem. These agents are improved by evolving neuromodulatory gene regulatory networks (GRN) that influence the learning and memory of agents. Agents trained by these neuromodulatory GRNs can consistently generalize better than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In this work we use an evolutionary algorithm to optimize gene-regulatory networks (GRNs) that dynamically tune the parameters of a reinforcement learning (RL) algorithm. This geneticallyregulated neuromodulation (GRNM) extends previous results that showed GRNM can enhance the learning of agents beyond traditional fixed parameter RL [15]. We apply GRNM to additional problem classes, and show that GRNs evolved Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…In this work we use an evolutionary algorithm to optimize gene-regulatory networks (GRNs) that dynamically tune the parameters of a reinforcement learning (RL) algorithm. This geneticallyregulated neuromodulation (GRNM) extends previous results that showed GRNM can enhance the learning of agents beyond traditional fixed parameter RL [15]. We apply GRNM to additional problem classes, and show that GRNs evolved Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionsupporting
confidence: 57%
“…An extensive review of computational models of neuromodulation can be found in [12], and some recent models are reviewed in [19]. In this study we extend work on the evolution of neuromodulation [15], focusing on the relationship between evolved neuromodulatory GRNs and reinforcement learning.…”
Section: Neuromodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has begun to make a connection between learning and genetic regulation. In [64], the authors studied a robot navigation problem with a robot controlled by a temporal-difference reinforcement learning agent. By introducing a neuromodulatory system governed by a GRN to control the agent's learning and memory, the robot was able to outperform traditional reinforcement learning.…”
Section: Neuromodulationmentioning
confidence: 99%
“…Now, GRNs are becoming ubiquitous models in artificial life and robotics. GRNs are the basis of a number of developmental models [3]- [5], as controllers of virtual and real robots [6]- [10], and neuromodulators of learning behavior [11], [12]. Other related methods of encoding reaction networks are commonly applied to similar problem domains [13]- [15].…”
mentioning
confidence: 99%